Guanxi Sebagai Budaya Pada Bisnis Online Shop Dalam Meningkatkan Perekonomian di Kabupaten Asahan - Ismail Ismail; Sakti Ritonga (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2022)
Guanxi is a network or relationship, belief, culture in Chinese ethnicity. This article analyzes the practice of Guanxi as a culture in the online shop business in improving the economy. This article aims to describe the practice of Guanxi as a culture in an online shop business. This study uses qualitative research with an ethnographic approach. The data collection of this research was carried out by in-depth interviews, participatory observation, and literature study. The results of this study indicate that the practice of Guanxi in the online shop business begins with building a network or relationship by creating a Whatsapp reseller group; how to build reseller trust by providing friendly, trustworthy, and cheap service according to the Fatih Olshop tagline. Building and maintaining trust between online shops is the key to online business success. By creating a reseller group, online shop actors do not work alone and can grow rapidly. In conclusion, the practice of Guanxi in the online shop business is a new culture that must be carried out. Building a network or relationship and maintaining trust is the key to the success of the business. However, practicing Guanxi as a culture in online business is not easy, but it takes strategy, hard work, and patience.